IMR 665: management of audio visual records & archives. Individual assignment: article summary / Muhammad Nazrin Amin Rudin - Amin Rudin, Muhammad Nazrin (2015)
The purpose of this paper is to summarize the comparison between two articles about the management of audio visual records. The core of the collection has been collected and gathered through the comparison between the two articles research that related with the main purpose of the paper. This article summary also is more focus on the related discussion between the articles. The training and skills that received by the archivists and record officers are important to support the roles and responsibilities to handle, conserve and preserve the audio visual records. Furthermore, archivists and records officers with limited training, skills and knowledge in managing audio visual records will prevent them from developing the policies and standard procedures of audio visual records management which is one of the main parts of the responsibilities of archivist and record officers. The paper would be helpful in determine the objectives and discussions of both articles, This article summary as well encourage and boost the knowledge and skills of archivists or records officers in managing the audio visual records.